Question #bfc9a

2 Answers
Feb 12, 2018

x=0,2pix=0,2π

Explanation:

Your question is

cos(x-pi/6) + cos(x+pi/6) = sqrt3cos(xπ6)+cos(x+π6)=3 in the interval [0,2pi][0,2π].

We know from trig identities that

cos(A+B) = cosAcosB-sinAsinBcos(A+B)=cosAcosBsinAsinB
cos(A-B) = cosAcosB+sinAsinBcos(AB)=cosAcosB+sinAsinB

so that gives

cos(x-pi/6) = cosxcos(pi/6)+sinxsin(pi/6)cos(xπ6)=cosxcos(π6)+sinxsin(π6)
cos(x+pi/6) = cosxcos(pi/6)-sinxsin(pi/6)cos(x+π6)=cosxcos(π6)sinxsin(π6)

therefore,

cos(x-pi/6)+cos(x+pi/6)cos(xπ6)+cos(x+π6)
=cosxcos(pi/6)+sinxsin(pi/6)+cosxcos(pi/6)-sinxsin(pi/6)=cosxcos(π6)+sinxsin(π6)+cosxcos(π6)sinxsin(π6)
=2cosxcos(pi/6)=2cosxcos(π6)

So we now know we can simplify the equation to

2cosxcos(pi/6) = sqrt32cosxcos(π6)=3

cos(pi/6) = sqrt3/2cos(π6)=32

so

sqrt3cosx = sqrt3 -> cosx = 13cosx=3cosx=1

We know that in the interval [0,2pi][0,2π], cosx=1cosx=1 when x=0, 2pix=0,2π

Feb 12, 2018

"No soln. in "(0,2pi)No soln. in (0,2π).

Explanation:

cos(x-pi/6)+cos(x+pi/6)=sqrt3cos(xπ6)+cos(x+π6)=3

Using, cosC+cosD=2cos((C+D)/2)cos((C-D)/2)cosC+cosD=2cos(C+D2)cos(CD2),

2cosxcos(-pi/6)=sqrt32cosxcos(π6)=3,

:. 2*sqrt3/2*cosx=sqrt3,

:. cosx=1=cos0.

Now, cosx=cosy rArr x=2kpi+-y, k in ZZ.

:. cosx=cos0 rArr x=2kpi, k in ZZ, i.e.,

x=0,+-2pi, +-4pi,...

:." The Soln. Set" sub (0,2pi)" is "phi.